INFLUENCE OF DRY BAKING YEAST FOLIAR SPRAY AND EGGSHELL POWDER AMENDMENT ON SELECTED GROWTH TRAITS OF BROCCOLI - Al-Alwani, Hadeer Abd-Alkadhim Hamza; Laftta, Wafaa M.; Atab, Huda A.; Merhj, Mohammed Y. (Journal of Geography, Regional Planning and Development, 2025)
Objective:  An experiment was conducted during the 2020–2021 winter growing season to investigate the effects of eggshell powder and dry yeast solution on the physiological and morphological traits of broccoli. Method: Under carefully regulated under which broccoli seeds were originally planted before being transferred to the field. The study evaluated plant height, total number of leaves, and percentage of dry matter in inflorescences. Results: Plant growth parameters were found to be considerably and favorably effected by both dry yeast and eggshell powder. This combination of 2 g/L dry yeast and 10 g/plant eggshell powder produced the highest dry matter content in the inflorescences (15.78%), the highest plant height (56 cm), and the most leaves (23.06). Novelty: The combination of dry yeast and eggshell powder significantly enhances the physiological and morphological traits of broccoli, demonstrating an effective and practical approach for improving broccoli growth parameters.